(untitled) (American Journal of Interdisciplinary Research and Development, 2022)
Communication is a person’s need as a social, conscious being, as a carrier of consciousness. We observe the separation of different high animal and human lifestyles into two sides: connections with nature and connections with living beings. The first type of contacts was called activity as a special type of human activity. The second type of communication is determined by the fact that the parties interacting with each other are living creatures that exchange information. This type of intra-species and interspecific communication is called communication. In this article, opinions and reflections are made on the specific importance of teachers’ ability to communicate successfully and the impact they have on students’ mastery of classes.